Exploring the Spatiotemporal Evolution and Influencing Factors of Shooting Incidents in the United States - Yang, Zhuo; Li, Gang; Nie, Qifan; Lin, Zhe (International Journal of Criminology and Sociology, 2025)
Drawing on data from the Gun Violence Archive, this study employs mathematical statistics, spatial analysis, and regression analysis to investigate the essential characteristics, spatiotemporal distribution, and influencing factors of shooting incidents in the United States from 2014 to 2023. The key findings are as follows:1) Demographically, the victims of shootings are predominantly male and older youths. Notably, indirect victimization is more prevalent among older youths, non-white youths (especially African American youths), those from higher-income households, and urban residents. 2) Temporally, there has been a rising trend in U.S. shootings over the decade from 2014 to 2023, with a pronounced increase during the pandemic period of 2019-2023. On a monthly basis, the incidence of shootings peaks from May to July. 3) Spatially, shooting incidents are largely concentrated in coastal regions, decreasing in frequency towards inland areas. Hotspots for shootings include states such as Texas, California, Louisiana, and Florida, followed by Indiana and New York.4) Various factors significantly influence the occurrence of shooting incidents, including family environment, ethnocultural context, residential conditions, business economy, and economic indicators.